Rescue of a Stranded Whale in the Palk Strait, Tamilnadu - Ramachandran, A. (Indian Forester, 2001)
An individual of Bryde’s Whale, Balaenoptera edeni which is a Schedule I species underthe Indian Wildlife Act, got stranded and struck in the deep mud along the coast of Palk Strait in Tamil Nadu. It was rescued alive and released into the deep sea by the Forest Department, Tamil Nadu with the support of various government agencies including District Administration, Fisheries and Police Department, Indian Navy and Coast Guard. This rescue operation was first of its kind in Coastal regions of Asian countries. The entire operation was successfully completed utilising only local materials and expertise. This operation indicated that Whale rescue is possible with indigenous technology at a cheaper cost and a non-sectoral and joint effort is needed for the conservation and management of endangered marine mammals.